TEKNIK MENINGKATKAN DAN MEMPERLANCAR PRODUKSI ASI PADA IBU POST SECTIO CAESARIA - Mas´adah Mas´adah; Rusmini Rusmini (Jurnal Kesehatan Prima, 2015)
Abstract: The delivery process through action section caesaria cause difficulties mothers initiate breastfeeding early because of rooming –in, weakness and abdominal incision in the mothers condition. Besides the feeling of mother who does not believe can provide care to the baby because the condition will cause a decrease in the hormone oxytocin that breast milk can not exit immediately after delivery. This can adversely affect a babys life because it lost the opportunity to obtain the highest nutrition early in life that colostrum. Proper lactation management can be applied if the nurse as care giver is able to understand the technique stimulates oxytocin expenditure. Based on the results of research there are several alternative methods that can be done to stimulate the hormne oxytocin t increase milk production after section caesaria. So that mothers can still provide breast milk to their babies in quality  among them is oxytocin massage methods, techniques marmet, warm compresses, massase rolling, breast care and SPEOS methods.